2012
DOI: 10.1111/j.1445-2197.2012.06185.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologies of the appendix: a 10‐year review of 4670 appendicectomy specimens

Abstract: There is a higher incidence of negative appendicectomies in women compared with men, which is similar to other published studies. Faecoliths and worms are a known cause of appendiceal colic and in our series were identified mostly in the absence of histological evidence of appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 12 publications
(16 reference statements)
7
60
2
2
Order By: Relevance
“…Additionally, similar results were obtained , Kalliakmanis et al 9 and Chandrasegaram et al 10 Those series stated that appendicitis is higher in the second decade. However, different results are concluded by Makaju et al 4 and Zulfikar et al…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Additionally, similar results were obtained , Kalliakmanis et al 9 and Chandrasegaram et al 10 Those series stated that appendicitis is higher in the second decade. However, different results are concluded by Makaju et al 4 and Zulfikar et al…”
Section: Discussionsupporting
confidence: 78%
“…Nonspecific symptoms and laboratories, delayed admission, communication problems, and socioeconomic factors were hypothesized to be the cause of higher perforation rate, especially in younger age and elderly. 3,19 There were two distinctive patterns of perforated appendicitis in this study, consistent with the study conducted by Chandrasegaram et al 10 which showed gradual decrease of perforation rate from the first to third decade and an advance of perforation rate with age. The latter can be seen in this study by the consistent high rates of perforation in >30 years groups.…”
Section: 17supporting
confidence: 81%
See 3 more Smart Citations